If two functions are inverse to each other, then they will undo each other.
That is,
(f∘g) (x) = x and (g∘f) (x) = x
Check the pair of functions are inverses to each other.
Example 1 :
f(x) = 4x + 3 and g(x) = (x - 3)/4
Solution :
Finding (f∘g) (x) :
(f∘g) (x) = f(g(x))
Finding (g∘f) (x) :
(g∘f) (x) = g(f(x))
So, the functions f(x) and g(x) are inverse to each other.
Example 2 :
f(x) = x3 + 1 and g(x) = ∛(x-1)
Solution :
Finding (f∘g) (x) :
(f∘g) (x) = f(g(x))
Finding (g∘f) (x) :
(g∘f) (x) = g(f(x))
So, the functions f(x) and g(x) are inverse to each other.
Example 3 :
f(x) = √(x - 3) and g(x) = x2 + 3, x ≥ 0
Solution :
Finding (f∘g) (x) :
(f∘g) (x) = f(g(x))
Finding (g∘f) (x) :
(f∘g) (x) = f(g(x))
So, the functions f(x) and g(x) are inverse to each other.
Example 4 :
f(x) = (4x + 4)/(x + 5) and g(x) = (4 - 5x)/(x - 4)
Solution :
Finding (f∘g) (x) :
(f∘g) (x) = f(g(x))
Finding (g∘f) (x) :
(g∘f) (x) = g(f(x))
So, the functions f(x) and g(x) are inverse to each other.
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM